Reasonable Incomplete Myocardial Revascularization in Patients with Chronic Heart Failure and Reduced Left Ventricular Ejection Fraction - Mariia V. Kucheriava; Georgiy B. Mankovsky (Український журнал серцево-судинної хірургії, 2022)
The aim. To evaluate the results of incomplete myocardial revascularization with percutaneous coronary intervention (PCI) in patients with ischemic cardiomyopathy and heart failure with reduced left ventricular ejection fraction based on the residual SYNTAX Score (rSS) scale.